MARKETING STRATEGY OF MSMES BASED ON SWOT ANALYSIS: A CASE STUDY ON THE BASIC NEEDS BUSINESS “SAHABAT SAYUR” IN NGIMBANG VILLAGE, LAMONGAN - Khoiruddin, Akhmad; Arifin, Syamsul; Utomo, Priyo; Siswohadi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to analyze the marketing strategy of the UMKM “Sahabat Sayur” in Ngimbang Village, Lamongan Regency, using a SWOT analysis approach. Data sources were obtained from three key informants directly involved in the business operations. Data collection techniques included in-depth interviews, direct observation, and documentation. The data analysis method used was descriptive qualitative analysis. The results showed that the main strengths of the UMKM include a strategic location, product variety and quality, and good relationships with customers. Weaknesses include limited capital, suboptimal digital promotion, and minimal financial record-keeping. Opportunities arise from increased public awareness of healthy food consumption, online shopping trends, and government support. Threats include competition from similar businesses, price fluctuations, and changes in government policy.